Exploring Methods for the Detection and Analysis of Antidiabetic Drugs in Pharmaceutical Formulations - Mande, Shounak; Gunjal, Shweta; Yadnik, Yogita; Patil, Chandrashekhar; Borse, Laxmikant; Dube, Pritam (Journal of Neonatal Surgery, 2025)
Analytical methods are employed for determining the chemical or physical properties of an analyte, chemical substance, chemical element, or mixture. Various analytical techniques are employed in the pharmaceutical industry to estimate the qualitative and quantitative concentration of drugs in biological fluids, including human plasma, serum, urine, as well as in their formulations, including tablets, capsules, and bulk drugs. (1) The objective of this analysis is to present an overview of the current analytical methods for the analysis of Peroxisome proliferator activated (PPAR) agonist as well as Dipeptidyl peptidase-4 (DPP4) inhibitor. The review is based on the estimation of Sitagliptin, Saxagliptin, Alogliptin, Gemifibrozil, Troglitazone, Pioglitazone, Linagliptin, and Rosiglitazone in active pharmaceutical ingredients, biological fluids, as well as various formulations, as reported in a variety of research articles. The analytical techniques that are employed to estimate these drugs include RP-HPLC, HPTLC, UPLC-MS/MS, LC-MS/MS, MALDI-TOF mass spectrometry, Raman spectroscopy, Liquid chromatography, Tandem mass spectrometry, TLC-densitometry with fluorescent detector, and LC-ESI-MS-MS (2). In this paper, UV Spectroscopy, HPLC, and HPTLC methods were studied. By referring to tabulated extensive conditions, the review assists in the appropriate selection of analytical technique, mobile phase, column, and detector based on the available analytical instruments and chemicals. Hypoglycemia, weight loss, and type 2 diabetes are all treated with DPP4 inhibitors. PPAR agonists are also employed in the treatment of type 2 diabetes, with the primary objective of reducing triglycerides as well as blood sugar levels in metabolic syndrome. (3)